ChemInform Abstract: Oxidation of Benzyl Alcohols to Benzaldehydes in Water Catalyzed by a Cu(II) Complex with a Zwitterionic Calix[4]arene Ligand. Issue 49 (December 2015) - Gao, Jun; Ren, Zhi‐Gang; Lang, Jian‐Ping
Abstract: The use of the Cu‐calixarene complex (CAL) in combination with TEMPO allows a high yielding oxidation of benzylic alcohols to the corresponding aldehydes with hydrogen peroxide as the oxidant.